Too early, too fast? The regulation of the eBook market in France and its possible effects on EU libraries - Respingue-Perrin, Sébastien (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
Until now, legislative interventions on ebooks and libraries have been applied to massive digitization. France went further, with global regulations of the ebooks' market. Beyond the French “cultural exception”, the ebook price-fixing law of May 26th, 2011 and the decrease from the ebook VAT rate decided in 2012 will have deep effects on this sector and, perhaps, could prevent the strains between publishers and libraries seen in the USA.Above all, legal rules have an impediment: what is an ebook?The French Parliament laid the foundations for the debate. Now, the answers are depending on the EU authorities, who have to define a clear policy.The ongoing discussions could have a major consequence: is the ebook, becoming a juridical object, subjected to the “digital renting and lending right”, in line with the 2006 Council directive? This may be the first step towards a regulation of the European libraries market.